The child in international refugee law - Pobjoy, Jason M. (Cambridge asylum and migration studies, 2017)
"Children are the victims of some of the most devastating examples of state-sanctioned and private human rights abuse. In increasing numbers, they are attempting to find international protection, and are forced to navigate complex administrative and legal processes that fail to take into account their distinct needs and vulnerabilities.
Keywords: Barnkonventionen : (1989); Konventionen om barnets rättigheter : (1989); Yleissopimus lapsen oikeuksista : (1989); Convention on the Rights of the Child : (1989 November 20); Convention Relating to the Status of Refugees : (1951 July 28); Refugee children : Legal status, laws, etc; Children (International law); International law and human rights; pakolaiset : lapset; lapsen oikeusasema; ihmisoikeudet : lapset; pakolaiset : kansainvälinen oikeus; Yleissopimus lapsen oikeuksista, CRC; non-refoulement, palauttamiskielto; lapsen etu -periaate